Global Profiling of Phosphorylation Reveals the Barley Roots Response to Phosphorus Starvation and Resupply - Ma, Zengke; Wang, Juncheng; Li, Chengdao; Ren, Panrong; Yao, Lirong; Li, Baochun; Meng, Yaxiong; Ma, Xiaole; Si, Erjing; Yang, Ke; Shang, Xunwu; Wang, Huajun (Frontiers in Plant Science, 2021)
Phosphorus（P）deficiency is a major threat to crop production, and understanding the response mechanism of plant roots P stress may facilitate the development of crops with increased tolerance. Phosphorylation plays critical roles in the regulation of proteins for plant responses to biotic and abiotic stress; however, its functions in P starvation/resupply are largely unknown for barley (Hordeum vulgare) growth. Here, we performed a global review of phosphorylation in barley roots treated by P starvation/resupply. We identified 7710 phosphorylation sites on 3373 proteins, of which 76 types of conserved motifs were extracted from 10,428 phosphorylated peptides. Most phosphorylated proteins were located in the nucleus (36%) and chloroplast (32%). Compared with control, 186, 131 and 156, 111 phosphorylated proteins showed significant differences at 6 and 48 h under P starvation and resupply conditions, respectively. These proteins mainly participated in carbohydrate metabolism, phytohormones, signal transduction, cell-wall stress, and oxidases stress. Moreover, the pathways of ribosome, RNA binding, protein transport and metal binding were significantly enriched under P starvation, and only two pathways of ribosome and RNA binding were greatly enriched under Pi resupply according to protein-protein interaction analysis. The results suggested that the phosphorylation proteins might play important roles in metabolic processes of barley roots in response to Pi deficiency/resupply. The data not only provide unique access to phosphorylation reprogramming of plant roots under deficiency/resupply, but also demonstrate the close cooperation between these phosphorylation proteins and key metabolic functions.